﻿Assessment of pharmacy students' awareness and knowledge of the COVID-19 pandemic and vaccines in Jordan: A cross-sectional study at private universities - Ali Salama (Pensoft Publishers, 2023)
Introduction: The COVID-19 pandemic prompted a global effort in developing vaccines to combat the virus. While several COVID-19 vaccines have been authorized and distributed internationally, there is a lack of research on the knowledge and perceptions of pharmacy students regarding these vaccines in Jordan. Methods: A cross-sectional study was conducted among pharmacy students at a private university in Jordan from July 28 to August 5, 2022. A Google survey consisting of 12 questions was administered to 200 respondents. Results: The survey aimed to assess pharmacy students' understanding of COVID-19 clinical characteristics, transmission routes, precautionary measures, hazard control, and knowledge of the different types of COVID-19 vaccines available in Jordan. Literature review indicated that students primarily obtained information from social media (80%), written articles (20%), and television (10%). The overall score for students' awareness of COVID-19 and its vaccines was 85%. The majority of students (82%) demonstrated a high level of knowledge and awareness of the pandemic. However, their understanding of hypercoagulation as an adverse event of COVID-19 vaccination and mask-wearing practices in various settings was limited. Most students believed that effective immunization strategies could eradicate the virus. Conclusion: Our findings indicate that pharmacy students possess a good understanding of COVID-19 and its vaccines. To enhance infection prevention among future pharmacists, measures and public awareness campaigns should be implemented to promote knowledge about the benefits of immunization in combating the COVID-19 pandemic.